Enantioselective Hydrosilylation of Aromatic Alkenes Catalyzed by Chiral Bis(oxazolinyl)phenyl–Rhodium Acetate Complexes - Naito, Tatsuo; Yoneda, Takuma; Ito, Jun-ichi; Nishiyama, Hisao (Synlett, 2012)
Highly efficient and enantioselective hydrosilylation of aromatic alkenes catalyzed by the chiral rhodium acetate complexes with the bis(oxazolinyl)phenyl ligands has been reported that afforded chiral silane derivatives with up to 99% ee.
Keywords: asymmetric hydrosilylation; alkene; bis(oxazolinyl)phenyl; rhodium; hydrosilane